1999
DOI: 10.1161/01.str.30.4.780
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Injury and Left Ventricular Performance After Subarachnoid Hemorrhage

Abstract: Background and Purpose-Electrocardiographic abnormalities and elevations of the creatine kinase myocardial isoenzyme (CK-MB) occur frequently after subarachnoid hemorrhage. In some patients, a reversible and presumably neurogenic form of left ventricular dysfunction is demonstrated by echocardiography. It is not known whether cardiac injury of this type adversely affects cardiovascular hemodynamic performance. Methods-We retrospectively studied 72 patients admitted to our neuro-ICU for aneurysmal subarachnoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
154
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(167 citation statements)
references
References 52 publications
7
154
2
4
Order By: Relevance
“…Myocardial dysfunction is related to the severity of subarachnoidal hemorrhage [31]. Myocardial dysfunction may have influenced renal function and water clearance in our study as well.…”
Section: Discussionsupporting
confidence: 48%
“…Myocardial dysfunction is related to the severity of subarachnoidal hemorrhage [31]. Myocardial dysfunction may have influenced renal function and water clearance in our study as well.…”
Section: Discussionsupporting
confidence: 48%
“…2 Myocardial stunning is reported following subarachnoid hemorrhage. 3 A total of 95% of cases in 1 series occurred in women. 2 Another series following subarachnoid hemorrhage found that all women were postmenopausal.…”
Section: Precipitating Factors and Clinical Featuresmentioning
confidence: 99%
“…2 Another series following subarachnoid hemorrhage found that all women were postmenopausal. 3 Patients present within 1 to 5 hours with chest pain or dyspnea. 2,4 Some develop pulmonary edema and cardiogenic shock.…”
Section: Precipitating Factors and Clinical Featuresmentioning
confidence: 99%
“…10) Various electrocardiography studies on rhythm disturbances have detected both minor abnormalities such as bradycardia, ST-T changes, and QTc prolongation, as well as less common but life-threatening arrhythmias such as ventricular tachycardia and ventricular fibrillation. 9,11) Cardiac muscle injury associated with SAH has been confirmed by histological findings of myofibrillar degeneration, myocytolysis, and inflammatory cell infiltration, 2,5) in addition to increased serum levels of myocardium-specific markers such as plasma phosphokinase myocardial fraction (CK-MB) 12) and troponin I. 26) Most patients also develop neurogenic pulmonary edema.…”
Section: Introductionmentioning
confidence: 95%